Vengeful Spirits, Divine Punishment, and Natural Disasters: Catastrophe and Religion in Japan - Hiroo, Sato (Religious studies in Japan, 2016)
Without scientific knowledge, the people of premodern societies in Japan tried to understand natural disasters through their association with transcendent beings (kami). In ancient Japan, natural disasters were interpreted as messages, that is, vengeful curses, from the kami. With the establishment of a systematic cosmology during the middle ages, the causes of catastrophes were explained in terms of the law of cause and effect according to which punishment and salvation were delivered by the kami. With the onset of the early modern period, the sense of reality inherent in the perceptions of fundamental beings declined, and the salvation of the dead could no longer be entrusted to the other-worldly kami. People then came to terms with catastrophes as natural disasters that must be faced. Rituals and customs, carried out over long periods, were put in place to raise the dead to the status of ancestral spirits. In addition to a shift from the traditional world in which kami, the living, and the dead coexisted, to a shutting out of the latter group, the process of "modernization" brought with it a restructuring of society around the exclusive rights and interests of human beings. The Great East Japan Earthquake has been an opportunity to reconsider the path ahead, and to reconsider responses to catastrophe which display the modern tendency to focus on the concerns of the living to the exclusion of those of the dead.